ARTERIAL HYPERTENSION IN WOMEN OF FERTILE AGE: PREDICTIVE VALUE OF ENDOTHELIN-1 AND LIFESTYLE RISK FACTORS - Mukhabbat A. Nigmatullaeva; Shakhlo Sh. Tilloeva (Modern American Journals, 2025)
Arterial hypertension (AH) remains one of the most prevalent cardiovascular conditions, with rising incidence among women of reproductive age due to metabolic and lifestyle changes.
Keywords: Arterial hypertension, women, prevention, endothelin-1, cardiovascular risk, reproductive age, ROC analysis